The structuralist revenge: economic complexity as an important dimension to evaluate growth and development - Gala, Paulo (2016)
This paper brings elements from the economic complexity literature to the discussions of the structuralist tradition on the central role of manufacturing and productive sophistication to economic growth. Using data provided by the Atlas of Economic Complexity this study sought to verify if countries’ complexity is important to explain convergence and divergence among poor and rich countries and, if so, which are the countries that will be able to reduce the income gap compared to developed countries. The econometric analysis revealed that exports and production complexity is significant to explain convergence and divergence among countries.